2016
DOI: 10.15740/has/ijas/12.2/326-334
|View full text |Cite
|
Sign up to set email alerts
|

Performance of different sources of organic manures in comparison with RDF and INM on nutrient uptake, nutrient balance and soil properties in rice-greengram cropping sequence

Abstract: during samba (August-December) season of 2012 and 2013 to study the effect of different sources of organic manures in comparison with INM and RDF on nutrient uptake and soil properties in rice (Oryza sativa L.). The experiment consisted of fourteen treatments which were laid out in Randomized Block Design, replicated thrice and SRI method of planting was adopted during both the years. Among fourteen treatments, four treatments with different organic manures at 100 per cent RDN on equi nutrient basis (farm yard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The negative K balance in the soil indicated that non-exchangeable form of K was released as a result of priming action of applied K. The net K loss was higher in DSR (-18.8 kg/ha), organic management in rice (-17.7 kg/ha) and 75% STBF in groundnut (-20.4 kg/ha) attributed to luxurious consumption of K by crops. Similar results with INM practice (RDF+green manuring) in rice-greengram cropping system was reported by Alagappan and Venkitaswamy (2016).…”
Section: Resultssupporting
confidence: 87%
“…The negative K balance in the soil indicated that non-exchangeable form of K was released as a result of priming action of applied K. The net K loss was higher in DSR (-18.8 kg/ha), organic management in rice (-17.7 kg/ha) and 75% STBF in groundnut (-20.4 kg/ha) attributed to luxurious consumption of K by crops. Similar results with INM practice (RDF+green manuring) in rice-greengram cropping system was reported by Alagappan and Venkitaswamy (2016).…”
Section: Resultssupporting
confidence: 87%
“…This might be due to positive response of green manuring with inorganic fertilizers on soil N status and may be attributed to N mineralization from organic sources or by retaining N in labile microbial pool with the changing microbial flush. The most soil conditions might have helped the mineralization of soil N and greater multiplication of soil microbes, which could convert organically bound nitrogen into readily available form leading to building up of higher available N. The inclusion of green manure (Sesbania aculeate) in rice based cropping sequence reduced the loss of native nitrate N accumulated during aerobic cycle of the rice based cropping sequence and also conserved nitrate nitrogen, which would be lost upon flooding [4].…”
Section: Nitrogenmentioning
confidence: 99%
“…This might be due to positive response of green manuring with inorganic fertilizers on soil N status and may be attributed to N mineralization from organic sources or by retaining N in labile microbial pool with the changing microbial flush. The moist soil conditions might have helped the mineralization of soil N and greater multiplication of soil microbes, which could convert organically bound nitrogen into readily available form leading to building up of higher available N. The inclusion of green leaf manure (Sesbania aculeata) in rice based cropping sequence reduced the loss of native nitrate N accumulated during aerobic cycle of the rice based cropping sequence and also conserved nitrate nitrogen, which would be lost upon flooding [6]. Increase in available P with FYM application and green manuring might be due to additional application of P and mobilization of P in the soil.…”
Section: Available Nitrogenmentioning
confidence: 99%